Islamic and conventional equity index co-movement and volatility transmission: Evidence from Pakistan - Khalil Jebran; Shihua Chen; Muhammad Zubair Tauni (Future Business Journal, 2017)
This study investigates the Islamic and conventional Index integration over the period 3rd September, 2008 to 30th September, 2015. This study uses Johansen and Juselius cointegration method for exploring the long run association. The short run association is explored using VECM model. The volatility spillover dynamics is examined using the GARCH and EGARCH models. The robustness of the results is analyzed by using Granger causality method, Variance Decomposition method, and Impulse Response Function. The estimation results show significant long run and short run association between Islamic and Conventional index. Furthermore, this study finds asymmetric bidirectional volatility spillovers between Islamic and conventional index. The findings suggest that domestic investors have low diversification opportunities by adding both Islamic and conventional index in their portfolios. However, international investors can add one of the indices in their portfolios, in order to benefit from portfolio diversification.
Keywords: 650; Conventional index; EGARCH; GARCH; Islamic index; Pakistan